Access and utilization of e-learning on tropical medicine at higher education institutions in Indonesia: A mixed-methods study - Eti Poncorini Pamungkasari; Atik Maftuhah; Susan Dierickx; Bulan Kakanita Hermasari; Vitri Widyaningsih; Yusuf Ari Mashuri; Adaninggar Angesti Laras; Anis Sofia Harjanti; Nada Syifa Al Biruni; Utiya Nabila Maulani; Sami Alcedo; Elsa Herdiana Murhandarwati; et al. (PLoS ONE, 2025)
Introduction This study explored the experiences of medical students and lecturers with e-learning online resources on tropical medicine in Indonesia to find opportunities to enhance medical education. Methods This was a mixed-methods study conducted between July and September 2022. The study involved academic staff and students from 13 universities in Indonesia. The universities were selected using stratified random sampling with consideration of accreditation level and geographical location. A survey with a structured self-reported questionnaire was conducted among 888 undergraduate and clinical medical students. For the qualitative study, 19 students and 12 academic staff participated in focus group discussions until data saturation was reached. Quantitative data were analysed descriptively, while thematic analysis was used to analyse the qualitative data. Results/discussion Our study found that most of pre-clinical students never accessed a specific e-learning platform for tropical medicine (68.2%, n = 345), meanwhile, the majority of clinical students had ever accessed e-learning platforms (51.6%, n = 197) for tropical medicine, thus showing a statistically significant difference (p-value of <0.001) between both groups. The most used resources to learn tropical medicine consisted of online journals by both pre-clinical (58.7%, n = 297) and clinical students (74.1%, n = 283). Online journals were said to help students a lot to understand tropical medicine concepts because of the quality information they provide. Google Scholar was the most common search engine used to seek information. While there was not yet a specific e-learning platform for tropical medicine, both pre-clinical (88.8%, n = 409) and clinical students (73.0%, n = 279) hoped for the improvement of e-learning platform quality (p-value of 0.006) that had existed. Students have the perception that e-learning has a role as a learning tool that can support them, especially clinical students, to reach their competence in tropical medicine, even though there are barriers related to infrastructural aspects, including internet access and limited user-friendly and local platforms on tropical medicine. Conclusion Preclinical and clinical students have the advantages of using e-learning on tropical medicine, even though there are some barriers related to access. However, specific e-learning platforms for tropical medicine are still very limited. Due to the importance of digital skills for the students as a medical professional in the future, there is an interest in developing a user-friendly e-learning platform specific for tropical medicine to facilitate medical students’ learning.